2011
DOI: 10.1016/j.etp.2010.05.006
|View full text |Cite
|
Sign up to set email alerts
|

RITA—Registry of Industrial Toxicology Animal data: The application of historical control data for Leydig cell tumors in rats

Abstract: Historical data for Leydig cell tumors from untreated or vehicle treated rats from carcinogenicity studies collected in the RITA database are presented. Examples are given for analyses of these data for dependency on variables considered to be of possible influence on the spontaneous incidence of Leydig cell tumors.In the 7453 male rats available for analysis, only one case of a Leydig cell carcinoma was identified. The incidence of Leydig cell adenomas differed markedly between strains. High incidences of clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…In other strains, much lower incidences have been reported from contract research organizations, that is, approximately 0.8% to 4% in SD and Wistar rats (Charles River 2004River , 2011Envigo 2016). Higher rates extracted from the Registry of Industrial Toxicology (RITA) database were reported by Nolte et al (2010) as 13.7% in Wistar-derived rat, continued breeding by Unilever (Nolte et al 2010). Most Leydig cell tumors are of a benign nature but may cause early sacrifice of the tumor bearers.…”
Section: Testesmentioning
confidence: 99%
“…In other strains, much lower incidences have been reported from contract research organizations, that is, approximately 0.8% to 4% in SD and Wistar rats (Charles River 2004River , 2011Envigo 2016). Higher rates extracted from the Registry of Industrial Toxicology (RITA) database were reported by Nolte et al (2010) as 13.7% in Wistar-derived rat, continued breeding by Unilever (Nolte et al 2010). Most Leydig cell tumors are of a benign nature but may cause early sacrifice of the tumor bearers.…”
Section: Testesmentioning
confidence: 99%
“…Leydig cell tubules have to be differentiated from hyperplasia and adenoma of the rete testis Rehm and Waalkes 1988). The spontaneous incidence of Leydig cell adenoma in rats seems to be inversely correlated to the body weight (Nolte et al 2010). Leydig cell hyperplasia and Leydig cell adenoma are readily induced in the rat by many xenobiotics from different chemical and therapeutic classes.…”
Section: Adenoma Leydig Cell (Figures 55-58): Testismentioning
confidence: 99%
“…In rats, the incidence of LCH/LCTs varies between strains. LCH/LCTs are common in F344 rats (incidence: close to 100%), but are rare in SD rats (incidence: ranging from 1 to 5%) 5 . Although SDT rats are an inbred strain of SD rats, there is a high incidence of LCH/LCTs in SDT rats.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, Leydig cell tumors (LCT) are particularly common in F344 rats, but are less frequent in SD rats 5 . Spontaneously Diabetic Torii (SDT) rats, an inbred strain of SD rats, are a well-known non-obese type 2 diabetic model that achieve diabetic status with high plasma glucose levels by 42 weeks of age 6 .…”
Section: Introductionmentioning
confidence: 99%